Boosting the antitumor efficacy over a nanoscale porphyrin-based covalent organic polymer via synergistic photodynamic and photothermal therapy. Issue 44 (14th May 2019) - Liu, Sainan; Liu, Ying; Hu, Chunling; Zhao, Xueyan; Ma, Ping'an; Pang, Maolin
Abstract : Enhanced antitumor efficacy was achieved for porphyrin-based covalent organic polymer nanoparticles via synergistic photodynamic and photothermal therapy. Abstract : Porphyrin-based covalent organic polymer nanoparticles were synthesized via a Schiff base reaction at room temperature. The resulting product showed a good photodynamic effect and a high photothermal conversion efficiency (34.88%). Both in vitro and in vivo experiments demonstrated the enhanced antitumor efficacy via synergistic photodynamic and photothermal therapy.